Leukocytoclastic vasculitis associated with nontyphoidal Salmonella in a patient infected with human immunodeficiency virus - Cornejo-Venegas, Gonzalo (2020)
A 27-year-old Peruvian woman living with human immunodeficiency virus (HIV) in clinical stage B3 and not on antiretroviral therapy presented with a ten-day history of fever, chills, night sweats and a two-day history of skin lesions. On physical examination, several erythematous-purplish lesions were found on the face and legs. Meningococcal infection was suspected and ceftriaxone was started. Blood culture grew nontyphoidal Salmonella enterica. A biopsy of the skin lesions showed leukocytoclastic vasculitis (LCV); therefore, corticosteroids were added. After two weeks of antibiotic and corticosteroid treatment, the lesions had resolved, but they recurred two days after treatment with prednisone was stopped. Corticosteroids and combination antiretroviral therapy were started simultaneously and the lesions resolved without recurrence. HIV infection has been associated with higher rates of skin lesions in salmonellosis. LCV has been described both in the setting of HIV infection and salmonellosis. However, our review of the literature found no previous cases of LCV in concurrent HIV and salmonellosis.